In Search of an Explanation for the Suffering of the Jews: Johann Reuchlin’s Open Letter of 1505 - Posset, Franz (Studies in Christian-Jewish Relations, 2011)
In 1505, the humanist Johann Reuchlin (1455-1522) published a booklet titled Doctor iohanns Reuchlins tütsch missiue, warumb die Juden so lang im ellend sind (Johann Reuchlin’s German-language open letter [discussing] why the Jews have been in “exile” so long). One may debate whether or not Reuchlin’s “German open letter” is to be understood as merely repeating the “conventional view that they [the Jews] were suffering for the sins of their forefathers who had mur-dered Jesus.” However, such an interpretation is a far too simplified summary of this rather unusual, “somewhat mysteri-ous tract.” Reuchlin felt sincere concern over the continued suffering of the Jews and sought to understand it for many years.